Penyusunan Anggaran Operasional sebagai Alat Pengendalian Biaya pada UMKM Pempek Love Palembang - Nabilah Angraini; Paisal Paisal; Afrizawati Afrizawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the process of preparing operational budgets in micro, small, and medium enterprises (MSMEs) of Pempek Love Palembang, which are engaged in the culinary sector typical of South Sumatra. Pempek Love Palembang is one of the business actors that plays a role in maintaining culinary traditions while contributing to the local economy. The research approach used is quantitative descriptive, with data collection techniques through direct interviews with business owners. Interviews are focused on operational activities that cover all stages of production to sales. The scope of analysis includes the preparation of various budget components, including sales budgets, production and inventory costs, raw material budgets, direct labor budgets, overhead costs, operational costs, cost of goods sold (COGS), and profit and loss budgets. Based on the findings, it is known that Pempek Love Palembang has not prepared a budget systematically and well documented. This is due to the limited knowledge of owners and employees about the concept of budget planning, so that the financial management process runs less than optimally. The absence of a structured budget makes it difficult to evaluate performance in a measurable manner and limits the ability of businesses to project profits accurately. This study confirms that the implementation of a good operational budget is not only beneficial for setting clear targets, but also serves as a cost control tool and a basis for strategic decision-making. With proper budget planning, MSMEs such as Pempek Love Palembang can increase efficiency, maintain financial stability, and expand business development opportunities in the future. The recommendation of this study is simple financial management training for MSME actors to be able to prepare budgets independently, accurately, and sustainably for more sustainable and stable business growth.